Answer:
The edge length will be equal to 4 inches.
Step-by-step explanation:
The volume of a cube = s * s * s (in which s represent side of the cube)
V = s * s * s
V = s³
64 = s³
64 = 4³
So edge length of the cube will be 4 inches.
Given:
One linear function represented by the table.
Another linear function represented by the graph.
To find:
The greater unit rate and greater y-intercept.
Solution:
Formula for slope (unit rate):
![m=\dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
From the given table it is clear that the linear function passes through (0,5) and (5,15). The function intersect the y-axis at (0,15), so the y-intercept is 15.
![m_1=\dfrac{15-5}{5-0}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B15-5%7D%7B5-0%7D)
![m_1=\dfrac{10}{5}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B10%7D%7B5%7D)
![m_1=2](https://tex.z-dn.net/?f=m_1%3D2)
So, the unit rate of first function is 2.
From the given graph it is clear that the linear function passes through (0,6) and (-4,0). The function intersect the y-axis at (0,6), so the y-intercept is 6.
![m_2=\dfrac{0-6}{-4-0}](https://tex.z-dn.net/?f=m_2%3D%5Cdfrac%7B0-6%7D%7B-4-0%7D)
![m_2=\dfrac{-6}{-4}](https://tex.z-dn.net/?f=m_2%3D%5Cdfrac%7B-6%7D%7B-4%7D)
![m_2=\dfrac{3}{2}](https://tex.z-dn.net/?f=m_2%3D%5Cdfrac%7B3%7D%7B2%7D)
So, the unit rate of first function is
.
Now,
![2>\dfrac{3}{2}](https://tex.z-dn.net/?f=2%3E%5Cdfrac%7B3%7D%7B2%7D)
![m_1>m_2](https://tex.z-dn.net/?f=m_1%3Em_2)
And,
![15>6](https://tex.z-dn.net/?f=15%3E6)
Therefore, the greater unit rate of the two functions is 2. The greater y-intercept of the two functions is 15.
Answer:
The Pythagorean identity states that
![\sin^2 t + \cos^2 t = 1](https://tex.z-dn.net/?f=%5Csin%5E2%20t%20%2B%20%5Ccos%5E2%20t%20%3D%201)
Using that we can rewrite the left denominator as:
![1 - \sin^2 t](https://tex.z-dn.net/?f=1%20-%20%5Csin%5E2%20t)
Which can be factored as
![(1 - \sin t)(1+ \sin t)](https://tex.z-dn.net/?f=%281%20-%20%5Csin%20t%29%281%2B%20%5Csin%20t%29)
The numerator we can expand as:
![(1 - \sin t)(1 - \sin t)](https://tex.z-dn.net/?f=%281%20-%20%5Csin%20t%29%281%20-%20%5Csin%20t%29)
On the right hand side, let's multply numerator and denominator with (1 - sin t):
The total formula then becomes:
![\dfrac{(1-\sin t)(1-\sin t)}{(1 - \sin t)(1 + \sin t)} = \dfrac{(1-\sin t)(1 - \sin t)}{(1+\sin t)(1 - \sin t)}](https://tex.z-dn.net/?f=%5Cdfrac%7B%281-%5Csin%20t%29%281-%5Csin%20t%29%7D%7B%281%20-%20%5Csin%20t%29%281%20%2B%20%5Csin%20t%29%7D%20%3D%20%5Cdfrac%7B%281-%5Csin%20t%29%281%20-%20%5Csin%20t%29%7D%7B%281%2B%5Csin%20t%29%281%20-%20%5Csin%20t%29%7D)
There you go... left and right are equal.
I think it is C it is probably wrong ☹️